Indonesia’s Role in ASEAN Peacebuilding through the ASEAN Outlook on the Indo-Pacific (AOIP) - Hasri Ainun (Indonesian Student Association Study Center in Türkiye, 2025)
This article explores Indonesia's strategic role in ASEAN peacebuilding and conflict prevention during the Joko Widodo (Jokowi) administration, focusing on the ASEAN Outlook on the Indo-Pacific (AOIP) as a strategic normative initiative. Anchored in Constructivism and supported by role theory, this study examines how Indonesia uses ASEAN-led institutional mechanisms to promote regional stability through shared norms and ASEAN identity amid escalating Indo-Pacific geopolitical tensions. Indonesia's efforts to uphold ASEAN's centrality and advance a rules-based regional order in order to preserve peace in the region are reflected in the AOIP/ Using a qualitative research method based on literature review and document analysis, the research investigates both official ASEAN documents and relevant academic literature. The findings of this article reveal that Indonesia's role in peacebuilding and conflict prevention is based on norm-based leadership, consistent with its identity as a bridge-builder and peace promoter. Despite concerns about Indonesia's diminishing involvement in ASEAN, AOIP illustrates how Indonesia has reframed its broader leadership role, through institutional innovation and normative diplomacy by emphasizing the centrality of ASEAN and its distinctive values. Furthermore, the wide acceptance of AOIP by regional and external powers demonstrates Indonesia's success in shaping a cooperative Indo-Pacific order and contributing to long-term peacebuilding through institutional engagement.